Integration and disintegration of EMU government bond markets - Christian Leschinski; Michelle Voges; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This paper analyzes market integration among long term government bonds in the Eurozone since the inception of the Euro in 1999. While it is commonly assumed that markets for EMU government bonds were closely integrated prior to the EMU debt crisis, we find that there is significant time variation in their relationship. There are periods of integration and disintegration, and differences between core and periphery countries can be observed long before the EMU debt crisis. To obtain insights into the sources of the observed time variation, we analyze the dependence on variables related to market sentiment, risk and risk aversion. The drivers of market integration are found to be similar to those for the well documented flight-to-quality effects from stocks to bonds, suggesting that in times of crisis investors do not only shift their portfolios from stocks to bonds, but there is also a stronger differentiation between more and less risky bonds. The persistence of these differentials leads to the conclusion that (at least in times of crisis) the pricing of EMU government bonds implied the possibility of macroeconomic and fiscal divergence between the EMU countries.
Keywords: G01; C32; C14; C58; E43; 330; EMU Debt Crisis; Flight-to-Quality; Fractional Cointegration; Market Integration; Yield Spreads